The Attitude Scale Towards Flirting Violence: ASTFV (International Journal of Scientific Research and Management (IJSRM), 2018)
The aim of this study was to develop an attitude scale towards flirting violence for university students who study at TED University. 232 university students aged 18-25 in Ankara participated in this study. University Students’ Attitudes Scale Towards Flirting Violence (ASTFV)” is a 5 item Likert type scale. Exploratory factor analysis and confirmatory factor analysis was used for validity and the results of the factor analysis indicated that the scale explains 62,798 % of the total variance. For reliability Cronbach Alpha coefficient was 0.938. Findings indicated that the ASTFV was a valid and reliable scale.